Silicon nitride powder and method for producing the same

CN122996034APending Publication Date: 2026-10-27DENKA CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202580023121.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-03-29
Filing Date
2025-03-24
Publication Date
2026-10-27

AI Technical Summary

Benefits of technology

根据本公开,能够提供一种氮化硅粉末,该氮化硅粉末能够制备威布尔系数较大且具有优异弯曲强度的烧结体。此外,根据本公开,还能够提供一种以更低成本制造上述氮化硅粉末的制造方法。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122996034A_ABST
    Figure CN122996034A_ABST
Patent Text Reader

Abstract

The present disclosure provides a silicon nitride powder, in a volume-based particle size cumulative distribution measured by a particle size distribution measuring device using a laser diffraction / scattering method, when a particle size at which an accumulated value from a small particle size side reaches 10% of the whole is set as D10, a particle size at which an accumulated value from a small particle size side reaches 50% of the whole is set as D50, a particle size at which an accumulated value from a small particle size side reaches 90% of the whole is set as D90, and a particle size at which an accumulated value from a small particle size side reaches 97% of the whole is set as D97, D97 is 2.0 μm or less, and (D90-D10) / D50 is 1.70 or less.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This disclosure relates to a silicon nitride powder and a method for manufacturing the same. Background Technology

[0002] Silicon nitride is a material with excellent strength, hardness, toughness, heat resistance, corrosion resistance, and thermal shock resistance. Therefore, it is used in various industrial parts such as die-casting machines and melting furnaces, as well as automotive parts. Furthermore, due to its excellent mechanical properties at high temperatures, silicon nitride is currently being researched for use in gas turbine components requiring high-temperature strength and high-temperature creep resistance. Patent Document 1 describes a silicon nitride sintered body characterized by a thermal conductivity of 100–300 W / (m·K) at room temperature and a three-point bending strength of 600–1500 MPa at room temperature.

[0003] Existing technical documents Patent documents Patent Document 1: Japanese Patent Application Publication No. 2004-262756 Summary of the Invention

[0004] The problem the invention aims to solve During the sintering of silicon nitride powder, silicon nitride particles first dissolve into the melt of the sintering aid, followed by silicon nitride re-precipitation and grain growth. During this process, a phase transformation occurs, converting to the more thermally stable β phase. The grain growth accompanying this phase transformation allows the silicon nitride powder to be sintered, forming a silicon nitride sintered body. Further improvements in the mechanical properties of silicon nitride sintered bodies are desired. Furthermore, when multiple sintered bodies are prepared using the same batch of silicon nitride powder, variations in quality (e.g., flexural strength) may occur between them. The Weibull coefficient is known to be used as an indicator of the degree of this variation, measured by assessing the flexural strength of multiple nitride sintered bodies. For example, a larger Weibull coefficient indicates a smaller variation in flexural strength between silicon nitride sintered bodies.

[0005] The purpose of this disclosure is to provide a silicon nitride powder capable of preparing sintered bodies with a high Weibull coefficient and excellent flexural strength. Furthermore, the purpose of this disclosure is to provide a method for manufacturing the aforementioned silicon nitride powder at a lower cost.

[0006] Methods for solving problems One embodiment of this disclosure provides the following silicon nitride powder.

[0007] [1] A silicon nitride powder, in the cumulative particle size distribution of a volume-based particle size distribution measured by a particle size distribution measuring device using laser diffraction and scattering method, is defined as follows: the particle size when the cumulative value from the small particle size side reaches 10% of the total is set as D10; the particle size when the cumulative value from the small particle size side reaches 50% of the total is set as D50; the particle size when the cumulative value from the small particle size side reaches 90% of the total is set as D90; and the particle size when the cumulative value from the small particle size side reaches 97% of the total is set as D97. D97 is below 2.0μm. (D90-D10) / D50 is below 1.70.

[0008] The silicon nitride powder in [1] has a D97 of less than 2.0 μm and a (D90-D10) / D50 of less than 1.70. Therefore, the silicon nitride powder is a silicon nitride powder with relatively small particle size and high particle size uniformity. When such silicon nitride powder is used as a raw material for sintered bodies, the environment can be homogenized when silicon nitride dissolves in the liquid phase of the sintering aid and precipitates again, thereby promoting the growth of silicon nitride particles with thermally stable β phase. In other words, when the above-mentioned silicon nitride powder is used as a raw material for sintered bodies, the generation of coarse particles in the prepared sintered body can be suppressed, and excellent bending strength can be achieved. Furthermore, since the above-mentioned silicon nitride powder itself has high uniformity, when multiple sintered bodies are prepared, the deviation in bending strength between sintered bodies can also be suppressed.

[0009] Furthermore, with conventional silicon nitride powders, when the powder contains silicon nitride with a thermally stable β phase, the β-phase silicon nitride does not melt and remains, preferentially acting as nuclei for crystal growth, resulting in uneven silicon nitride particle size distribution in the sintered body, and potentially containing coarse particles. When coarse particles are present in the sintered body, stress concentrates at these particles, leading to a decrease in the flexural strength of the sintered body. Moreover, due to the low homogeneity of the powder, quality deviations are easily introduced when preparing multiple sintered bodies. In contrast, the silicon nitride powder disclosed herein, because its D97 and (D90-D10) / D50 values ​​are within a predetermined range, can further suppress the formation of coarse particles in the sintered body, as described above; even when preparing multiple sintered bodies, it can suppress deviations in flexural strength between each sintered body, and can increase the Weibull coefficient.

[0010] The silicon nitride powder mentioned in [1] can also be any one of the following [2] to [4].

[0011] [2] The silicon nitride powder according to [1], wherein the α-oxidation rate is less than 96.0% by mass.

[0012] [3] The silicon nitride powder according to [1] or [2], wherein the oxygen content is 0.60 to 1.60% by mass.

[0013] [4] The silicon nitride powder according to any one of [1] to [3], wherein the BET specific surface area is 12.0 m². 2 / g or more.

[0014] [5] The silicon nitride powder according to any one of [1] to [4], wherein the oxygen content / (BET specific surface area × D10) is 0.30 to 0.80.

[0015] The silicon nitride powder mentioned above [2] has an α-saturation rate of less than 96.0% by mass. Since it is a silicon nitride powder with a low α-saturation rate, it can reduce the cost in the manufacturing process.

[0016] The silicon nitride powder in [3] above has an oxygen content of 0.60 to 1.60% by mass. The silicon nitride powder with the above oxygen content can improve the reactivity during the sintering process, suppress the formation of embrittlement phases in the sintered body caused by oxygen, and suppress the embrittlement of the sintered body itself. Therefore, it can further improve the bending strength of the sintered body.

[0017] The silicon nitride powder mentioned above [4] has a BET specific surface area of ​​12.0 m². 2 Silicon nitride powder with a BET specific surface area of ​​over / g has a larger contact area with the liquid phase of the sintering aid during sintering, thus dissolving more easily in the sintering aid. Therefore, the growth environment (growth field) for silicon nitride particles with the β phase can be made more uniform. Since the particle size of such silicon nitride powder tends to be more uniform, the Weibull coefficient can be further improved regarding the flexural strength of the sintered body.

[0018] The silicon nitride powder described above [5] has an oxygen content / (BET specific surface area × D10) of 0.30 to 0.80. Since the silicon nitride powder is composed of smaller particles when the oxygen content / (BET specific surface area × D10) of the silicon nitride powder is within the above range, the generation of coarse particles in the sintered body can be further suppressed when the powder is used as a raw material for sintered bodies. Furthermore, it is possible to achieve a higher level of sintering reaction promotion effect based on the oxygen content of silicon nitride particles and the contact area with the liquid phase of the sintering aid, as well as an inhibition effect on the formation of embrittled phase based on adjusting the oxygen content of silicon nitride particles. Therefore, the flexural strength of the sintered body obtained using the above-mentioned silicon nitride powder can be further improved.

[0019] One embodiment of this disclosure provides a method for manufacturing silicon nitride powder.

[0020] [6] A method for manufacturing silicon nitride powder, comprising a step of adjusting particle size, In the aforementioned process, in the cumulative particle size distribution based on volume measured using a particle size distribution measuring device based on laser diffraction and scattering, the particle size at which the cumulative value from the small particle size side reaches 10% of the total is defined as D10, the particle size at which the cumulative value from the small particle size side reaches 50% of the total is defined as D50, the particle size at which the cumulative value from the small particle size side reaches 90% of the total is defined as D90, and the particle size at which the cumulative value from the small particle size side reaches 97% of the total is defined as D97. To make D97 below 2.0μm, Furthermore, the particle size of the raw silicon nitride powder is adjusted by ensuring that (D90-D10) / D50 is below 1.70.

[0021] The silicon nitride powder manufacturing method described in [6] is a relatively simple method, which manufactures the target silicon nitride powder by adjusting the particle size of the raw silicon nitride powder. Therefore, compared with the manufacturing cost of silicon nitride powder with a high α-sizing rate, which is a raw material for sintered bodies that can exhibit excellent flexural strength, silicon nitride powder can be manufactured at a lower cost. In addition, the silicon nitride powder obtained by the manufacturing method described in [6] has high particle size uniformity because the particle size is adjusted so that D97 is 2.0 μm or less and (D90-D10) / D50 is 1.70 or less, and it can be used to manufacture sintered bodies with high flexural strength. Furthermore, by using the silicon nitride powder obtained by the manufacturing method described above, multiple sintered bodies with high Weibull coefficients and excellent flexural strength can also be manufactured.

[0022] The method for manufacturing silicon nitride powder in [6] above can also be as follows [7] or [8].

[0023] [7] According to the method for manufacturing silicon nitride powder described in [6], the step of adjusting the particle size is to use an air classifier to classify the raw silicon nitride powder under the condition of a swirling airflow velocity of 170 to 300 m / s to adjust the particle size.

[0024] [8] The method for manufacturing silicon nitride powder according to [6] or [7], wherein the α-oxidation rate of the raw silicon nitride powder is 96.0% by mass or less.

[0025] The silicon nitride powder manufacturing method described above [7] adjusts the particle size of the silicon nitride powder by classifying it under certain conditions using an air classifier. By adjusting the particle size of the silicon nitride powder through such classification, for example, compared with methods such as adjusting the particle size by mixing powders of different particle sizes or by pulverizing, this method can more easily produce the target silicon nitride powder.

[0026] The effects of the invention According to this disclosure, a silicon nitride powder can be provided that can be used to prepare sintered bodies with a large Weibull coefficient and excellent flexural strength. Furthermore, according to this disclosure, a method for manufacturing the aforementioned silicon nitride powder at a lower cost can also be provided. Attached Figure Description

[0027] Figure 1 This is a scanning electron microscope image showing the cross-section of a sintered body manufactured using silicon nitride powder from Comparative Example 4.

[0028] Figure 2 This is a scanning electron microscope image showing a cross-section of a sintered body manufactured using the silicon nitride powder of Example 4. Detailed Implementation

[0029] The embodiments of this disclosure are described below. However, the following embodiments are illustrative examples of this disclosure and are not intended to limit this disclosure to the following. The upper or lower limit of the numerical range disclosed in this disclosure may be replaced by any value shown in the embodiments. Furthermore, the separately listed upper and lower limit values ​​may be combined arbitrarily. The “~” symbol used in the numerical range indicates a numerical range that includes both the upper and lower limits. For example, “X~Y” means a numerical range of “X and below Y”. Unless otherwise stated, the materials or ingredients illustrated in this disclosure may be used alone or in combination of two or more.

[0030] <Silicon nitride powder> In one embodiment, the silicon nitride powder (Si3N4 powder) is defined as follows: in the cumulative particle size distribution measured using a particle size distribution measuring device based on volume, the particle size at which the cumulative value from the small particle size side reaches 10% of the total is defined as D10; the particle size at which the cumulative value from the small particle size side reaches 50% of the total is defined as D50; the particle size at which the cumulative value from the small particle size side reaches 90% of the total is defined as D90; and the particle size at which the cumulative value from the small particle size side reaches 97% of the total is defined as D97. In this case, D97 is 2.0 μm or less, and (D90 - D10) / D50 is 1.70 or less. By using such silicon nitride powder, a sintered body with a large Weibull coefficient and excellent flexural strength can be obtained.

[0031] In silicon nitride powder, in the cumulative particle size distribution based on volume measured using a particle size distribution measuring device based on laser diffraction and scattering, when the particle size at which the cumulative value from the small particle size side reaches 97% of the total is defined as D97, D97 is 2.0 μm or less. The aforementioned D97 can be, for example, 1.80 μm or less, 1.60 μm or less, 1.40 μm or less, 1.30 μm or less, or 1.25 μm or less. Silicon nitride powder with D97 in this range has a sufficiently small particle size. Even if silicon nitride powder with D97 in this range contains a large amount of β-phase, which easily becomes crystal nuclei during sintering, the particle size of each β-phase silicon nitride particle is small. Therefore, even if it becomes a crystal nucleus, there will not be a large particle size difference between it and the newly precipitated β-phase silicon nitride particles, thereby further suppressing the formation of coarse particles due to sintering. Therefore, the formation of coarse particles in the sintered body can be further suppressed. Such sintered bodies have higher flexural strength.

[0032] For example, D97 can be 0.80 μm or higher, 0.90 μm or higher, 1.00 μm or higher, 1.10 μm or higher, 1.15 μm or higher, 1.20 μm or higher, or 1.21 μm or higher. The range of D97 can be, for example, 0.80–2.0 μm, 0.80–1.80 μm, 0.80–1.60 μm, 0.80–1.40 μm, or 0.80–1.25 μm.

[0033] In the cumulative particle size distribution measured using a particle size distribution measuring device based on volume, D10 is defined as the particle size at which the cumulative value from the smallest particle size side reaches 10% of the total; D50 is defined as the particle size at which the cumulative value from the smallest particle size side reaches 50% of the total; and D90 is defined as the particle size at which the cumulative value from the smallest particle size side reaches 90% of the total. Then, (D90-D10) / D50 can be below 1.70, below 1.60, or below 1.50. The value of (D90-D10) / D50 is called the span value, which is an indicator of the breadth of the particle size distribution. The smaller the span value, the smaller the difference in particle size between D90 and D10, and the sharper (narrower) the particle size distribution. When the particle size distribution is sharper, the particle size uniformity of the powder is higher because the particle size deviation of the silicon nitride powder is smaller. Therefore, when multiple sintered bodies are prepared using silicon nitride powder with a (D90-D10) / D50 ratio within the aforementioned range, the deviation in flexural strength among the sintered bodies can be further reduced. Consequently, the Weibull coefficient regarding the flexural strength of the sintered body can be further improved. Furthermore, sintering can be made more uniform, and the formation of coarse particles in localized areas of the sintered body can be more effectively suppressed. Therefore, the flexural strength of the sintered body can be further improved.

[0034] The value of (D90-D10) / D50 can be, for example, 1.30 or higher, or 1.40 or higher. Silicon nitride powder with a lower limit of (D90-D10) / D50 within this range has a smaller particle size deviation. Therefore, during the manufacture of sintered bodies, the environment in which silicon nitride powder dissolves in the liquid phase of the sintering aid and precipitates again can be further homogenized, and the increase in particle size deviation of the β-phase particles during growth can be more effectively suppressed. Therefore, the flexural strength of the obtained sintered body can be further improved. The range of (D90-D10) / D50 value of the sintered body can be, for example, 1.30 to 1.70, or 1.40 to 1.70.

[0035] D90 can be below 1.50 μm, 1.30 μm, or 1.10 μm. Since silicon nitride powder with an upper limit D90 within this range is composed of smaller particles, using this powder as a raw material for sintered bodies can further suppress the formation of coarse particles, thereby obtaining sintered bodies with higher flexural strength. Furthermore, D90 can be, for example, above 0.30 μm, above 0.40 μm, above 0.50 μm, above 0.60 μm, above 0.70 μm, above 0.80 μm, or above 0.83 μm. When the lower limit D90 is within this range, excessive increase in oxygen content due to smaller particle size can be prevented, and the formation of embrittled phases during sintering can be further suppressed, thereby further improving the flexural strength of the sintered body. Furthermore, it can improve the production efficiency of grading, thereby enabling the manufacture of silicon nitride powder at a lower cost, and can stabilize manufacturing conditions such as sintering temperature during the sintering process. The D90 range can be, for example, 0.30–1.50 μm, 0.50–1.30 μm, or 0.60–1.10 μm.

[0036] For example, D50 can be 0.70 μm or less, 0.65 μm or less, 0.60 μm or less, or 0.58 μm or less. Since silicon nitride powder with an upper limit D50 within this range is composed of smaller particles, when this powder is used as a raw material for sintered bodies, the formation of coarse particles in the sintered body can be further suppressed, thereby obtaining a sintered body with higher flexural strength. Furthermore, D50 can be 0.20 μm or more, 0.30 μm or more, 0.40 μm or more, 0.45 μm or more, or 0.47 μm or more. When the lower limit D50 is within this range, excessive increase in oxygen content due to smaller particle size can be prevented, and the formation of embrittled phases during sintered body preparation can be further suppressed, thereby further improving the flexural strength of the sintered body. Furthermore, it can improve the production efficiency of grading, thereby enabling the manufacture of silicon nitride powder at a lower cost, and can stabilize manufacturing conditions such as sintering temperature during the sintering process. The D50 range can be, for example, 0.20–0.70 μm, 0.30–0.65 μm, 0.30–0.60 μm, or 0.30–0.58 μm.

[0037] For example, D10 can be 0.40 μm or less, 0.30 μm or less, or 0.20 μm or less. Since silicon nitride powder with an upper limit D10 within this range is composed of smaller particles, when this powder is used as a raw material for sintered bodies, the formation of coarse particles in the sintered body can be further suppressed, thereby obtaining a sintered body with higher flexural strength. Furthermore, D10 can be 0.02 μm or more, 0.05 μm or more, 0.10 μm or more, 0.12 μm or more, 0.14 μm or more, or 0.16 μm or more. When the lower limit D10 is within this range, excessive increase in oxygen content due to smaller particle size can be prevented, and the formation of embrittled phases during sintered body preparation can be further suppressed, thereby further improving the flexural strength of the sintered body. Furthermore, it can improve the production efficiency of grading, thereby enabling the manufacture of silicon nitride powder at a lower cost, and can stabilize manufacturing conditions such as sintering temperature during the sintering process. The range of D10 can be, for example, 0.05–0.30 μm, 0.10–0.20 μm, or 0.12–0.20 μm.

[0038] Laser diffraction and scattering can be performed according to the method described in JIS R 1629:1997 "Method for determination of particle size distribution of fine ceramic raw materials by laser diffraction and scattering". A laser diffraction and scattering particle size distribution measuring device (manufactured by Microtrac BEL, trade name: MT-3300EX) can be used for the determination.

[0039] The silicon nitride powder disclosed herein, by adjusting the values ​​of D97 and (D90-D10) / D50, enables the preparation of sintered bodies with excellent flexural strength even with a low α-saturation rate. The α-saturation rate (the mass ratio of α-Si3N4 to the total amount of Si3N4) of the silicon nitride powder can, for example, be 96.0% by mass or less, 95.0% by mass or less, or 94.0% by mass or less. When the α-saturation rate is within such a range, the proportion of the β phase in the silicon nitride powder is further increased, thus resulting in excellent production efficiency. The aforementioned α-saturation rate can also be, for example, 89.0% by mass or more, or 90.0% by mass or more. When the α-saturation rate is within such a range, sintered bodies with even better flexural strength can be obtained. The alpha conversion rate can range, for example, 89.0–96.0% by mass, 89.0–95.0% by mass, 89.0–94.0% by mass, 90.0–96.0% by mass, 90.0–95.0% by mass, or 90.0–94.0% by mass.

[0040] The alpha saturation of silicon nitride powder can be adjusted according to the conditions under which it is sintered. Silicon nitride powder with a high alpha saturation can be obtained through a chemical synthesis method using the thermal decomposition of imide, or through a high-temperature vapor-phase method involving crystal growth at high temperatures to form euhedral particles. These methods require chemical synthesis reactions that generate a large number of byproducts, resulting in higher costs. On the other hand, since silicon nitride powder with a lower alpha saturation can be obtained through the direct nitridation reaction of metallic silicon, cost increases can be suppressed, and manufacturing can be relatively simple. The alpha saturation of silicon nitride powder can be determined based on the intensity of X-ray diffraction lines. Specifically, the alpha saturation of silicon nitride powder is measured according to the method described in the examples.

[0041] The BET specific surface area of ​​silicon nitride powder can be, for example, 12.0 m². 2 / g or more, up to 13.0m 2 / g or more, and can also be 14.0m 2 Silicon nitride powders with a BET specific surface area of ​​ / g or higher have a larger contact area with the liquid phase of the sintering aid during sintering, making them more prone to dissolution. Therefore, due to the larger BET specific surface area, the uniformity of the growth environment for silicon nitride particles with the β phase can be further improved.

[0042] For example, the specific surface area of ​​BET can be 20.0 m². 2 Below / g, it can also be 18.0m 2 Below / g, it can also be 16.0m 2 Below / g, it can also be 15.0m 2Below / g. Although there is no technical upper limit to BET specific surface area, oxygen content generally increases with increasing BET specific surface area. Therefore, excessively high BET specific surface area leads to excessive oxygen content, resulting in the formation of an embrittled phase during sintering and causing a decrease in strength. In other words, silicon nitride powder with an upper limit to BET specific surface area within this range can maintain oxygen content within an appropriate range. Therefore, the flexural strength of the obtained sintered body can be further improved. The range of BET specific surface area can be, for example, 12.0–20.0 μm. 2 / g, 13.0~20.0m 2 / g or 14.0~20.0m 2 / g.

[0043] The BET specific surface area of ​​silicon nitride powder can be adjusted, for example, by changing the pulverization conditions during the manufacturing process of silicon nitride powder. The BET specific surface area in this disclosure is the value determined by the BET single-point method using nitrogen gas, according to the method described in JIS R 1626:1996 "Determination of specific surface area of ​​fine ceramic powders by gas adsorption BET method".

[0044] The oxygen content of silicon nitride powder can be, for example, 0.60 to 1.60% by mass. The oxygen content disclosed herein refers to the total oxygen content. Silicon nitride powder with such an oxygen content not only contains sufficient oxygen to promote sintering but also further suppresses the formation of embrittlement phases caused by excessive oxygen. Therefore, sintered bodies made from silicon nitride powder with such an oxygen content exhibit higher flexural strength. The oxygen content can be determined using a commercially available oxygen and nitrogen analyzer.

[0045] The oxygen content can be, for example, 0.70% by mass or more, 0.72% by mass or more, or 0.74% by mass or more. Silicon nitride powder with such an oxygen content contains sufficient oxygen, which can further promote the sintering reaction and further improve the flexural strength of the sintered body.

[0046] The oxygen content can be, for example, below 1.40% by mass, below 1.30% by mass, below 1.20% by mass, below 1.10% by mass, below 1.00% by mass, below 0.90% by mass, or below 0.80% by mass. Silicon nitride powder with such oxygen content can further suppress the formation of embrittlement phases caused by excessive oxygen during sintering, thereby further improving the flexural strength of the sintered body. The oxygen content range can be, for example, 0.70–1.60% by mass, 0.72–1.60% by mass, 0.74–1.60% by mass, 0.74–1.40% by mass, 0.74–1.20% by mass, 0.74–1.00% by mass, or 0.74–0.90% by mass.

[0047] The BET specific surface area of ​​silicon nitride powder can be 12.0 m². 2 The silicon nitride powder has a BET specific surface area of ​​12.0–20.0 m² / g or higher, and an oxygen content of 0.60% by mass or higher. Since both the BET specific surface area and the lower limit of the oxygen content are within the aforementioned range, a large amount of oxygen can be adsorbed on the surface of the silicon nitride particles, thereby further promoting the sintering reaction and enabling the production of sintered bodies with higher flexural strength. Furthermore, the BET specific surface area of ​​the silicon nitride powder can also be 12.0–20.0 m² / g. 2 / g, and the oxygen content can be 0.60 to 1.60% by mass. By keeping the BET specific surface area and oxygen content of silicon nitride powder within the above range, it is possible to achieve a higher level of sintering reaction promotion effect based on the oxygen content of silicon nitride particles and the contact area with the liquid phase of the sintering aid, as well as an inhibition effect on the formation of embrittled phase based on adjusting the oxygen content of silicon nitride particles.

[0048] The oxygen content / (BET specific surface area × D10) can also be 0.30 to 0.80. Since the silicon nitride powder will consist of smaller particles when the oxygen content / (BET specific surface area × D10) is within the above range, the formation of coarse particles in the sintered body can be further suppressed when using this powder as a raw material. Furthermore, it is possible to achieve a higher level of sintering reaction promotion effect based on the oxygen content of the silicon nitride particles and the contact area with the liquid phase of the sintering aid, as well as an inhibition effect on the formation of embrittled phases based on adjusting the oxygen content of the silicon nitride particles. Therefore, the flexural strength of the sintered body obtained using the above-mentioned silicon nitride powder can be further improved.

[0049] When the oxygen content / (BET specific surface area × D10) is above 0.80, the oxygen content may increase excessively due to the reduction in particle size, making the formation of embrittlement phases during sintering significantly, thus posing a risk of decreased flexural strength of the sintered body. When the oxygen content / (BET specific surface area × D10) is below 0.30, the formation of coarse particles in the sintered body may also pose a risk of decreased flexural strength.

[0050] <Method for manufacturing silicon nitride powder> One embodiment of a method for manufacturing silicon nitride powder includes a particle size adjustment step. In this step, based on the cumulative particle size distribution measured using a particle size distribution measuring device based on laser diffraction and scattering, the particle size at which the cumulative value from the small particle size side reaches 10% of the total is set as D10, the particle size at which the cumulative value from the small particle size side reaches 50% of the total is set as D50, the particle size at which the cumulative value from the small particle size side reaches 90% of the total is set as D90, and the particle size at which the cumulative value from the small particle size side reaches 97% of the total is set as D97. The particle size of the raw silicon nitride powder is adjusted such that D97 is 2.0 μm or less, and (D90-D10) / D50 is 1.70 or less. In this manufacturing method, using silicon nitride powder as a raw material and manufacturing the target silicon nitride powder by adjusting the particle size is a relatively simple method. Therefore, silicon nitride powder with a high α-saturation rate can be manufactured at a lower cost compared to the manufacturing cost of silicon nitride powder, which is a raw material for sintered bodies that can exhibit excellent flexural strength.

[0051] In the above-described method for manufacturing silicon nitride powder, the α-saturation rate of the raw silicon nitride powder can, for example, be 96.0% by mass or less. If such raw silicon nitride powder can be obtained, it can be used directly; alternatively, raw silicon nitride powder with an α-saturation rate of 96.0% by mass or less can be prepared separately and used. In other words, the method for manufacturing silicon nitride powder may include a step for preparing raw silicon nitride powder before the step of adjusting the particle size. The step for preparing raw silicon nitride powder may also include at least one step selected from the group consisting of a mixing step of mixing silicon-containing raw materials to obtain a mixture, a nitriding step of calcining the mixture to obtain a nitride, and a post-treatment step of treating the nitride with hydrofluoric acid. Raw silicon nitride powder can also be obtained by sequentially performing the mixing step, the nitriding step, and the post-treatment step.

[0052] In the mixing process, silicon powder, used as a raw material, is mixed with a fluoride. The fluoride mixed with the silicon powder acts as a nitriding aid that promotes nitriding. Examples of fluorides include those of Li, Na, K, Mg, Ca, Sr, and Ba. The amount of fluoride relative to 100 parts by mass of silicon powder can be 0.5 to 1.5 parts by mass. Without the addition of fluoride, nitriding is not promoted, and unreacted metallic silicon remains, resulting in a decrease in the purity of the raw silicon nitride powder and a reduction in production efficiency. The purity of the silicon powder mixed with the fluoride can be, for example, 99.0 to 99.9% by mass. Silicon powder with such purity can be obtained by treatment with a mixed acid containing hydrofluoric acid (HF) and hydrochloric acid (HCl).

[0053] In the nitriding process, a raw material containing silicon powder and fluoride is placed in a mixed atmosphere containing nitrogen and at least one gas selected from the group consisting of hydrogen and ammonia, and then fired to obtain a nitride. The total content of hydrogen and ammonia in the mixed atmosphere is, for example, 10% to 40% by volume, based on the overall mixed atmosphere. The firing temperature is, for example, 1100 to 1450°C or 1200 to 1400°C. The firing time is, for example, 30 to 100 hours.

[0054] In the post-processing step, the aforementioned nitride is treated with hydrofluoric acid, the concentration of which is, for example, 1.0 to 4.0% by mass. For example, silicon nitride powder can be dispersed in hydrofluoric acid for treatment. The concentration of hydrogen fluoride in the hydrofluoric acid can be, for example, 1.3 to 2.3% by mass. The temperature of the hydrofluoric acid in the post-processing step is, for example, 40 to 80°C. Furthermore, the time for immersing the aforementioned nitride in hydrofluoric acid is, for example, 1 to 10 hours.

[0055] Through the above-described preparation process of raw silicon nitride powder, the alpha saturation rate can be adjusted and raw silicon nitride powder can be prepared. This manufacturing method belongs to the so-called direct nitriding method, which can produce silicon nitride powder at a lower manufacturing cost compared to the imide method. Although the raw silicon nitride powder produced by the direct nitriding method has a lower alpha saturation rate and contains a certain amount of impurities, it not only suppresses manufacturing costs but also produces silicon nitride sintered bodies with high flexural strength, thus making it suitable for manufacturing the sintering raw silicon nitride powder disclosed herein.

[0056] The alpha fraction of the raw silicon nitride powder can be, for example, 96.0% by mass or less, 95.0% by mass or less, or 94.0% by mass or less. Silicon nitride powder with an alpha fraction within the above range is readily available and can be prepared due to its lower manufacturing cost and excellent production efficiency. According to the silicon nitride powder manufacturing method disclosed herein, even when using raw material powder with an alpha fraction within the above range, it is possible to provide a silicon nitride powder that can be used to manufacture sintered bodies with excellent flexural strength. The alpha fraction can also be 89.0% by mass or more, or 90.0% by mass or more. The range of the alpha fraction of the raw silicon nitride powder can be, for example, 89.0–96.0% by mass, 89.0–95.0% by mass, 89.0–94.0% by mass, 90.0–96.0% by mass, 90.0–95.0% by mass, or 90.0–94.0% by mass.

[0057] In the particle size adjustment process, the obtained silicon nitride powder is adjusted so that its D97 is below 2.0 μm and (D90-D10) / D50 is below 1.70. Examples of particle size adjustment methods include: adjusting particle size by mixing powders with different particle sizes, adjusting particle size by pulverizing, or adjusting particle size by grading.

[0058] When adjusting particle size through pulverization, the raw silicon nitride powder can be pulverized using either dry or wet methods (hereinafter also referred to as the "pulverization process"). The pulverization process can be carried out in multiple stages, such as coarse pulverization and fine pulverization. For example, the pulverization process may include two steps: ball milling and vibratory milling. Equipment such as ball mills, bead mills, and stirred mills can be used in the pulverization process.

[0059] In the grinding process, the filling rate of grinding balls in the container can be, for example, 30-70% by volume. The lower limit of the filling rate of grinding balls in the container is calculated based on the container's volume, and can be, for example, 50% by volume or 60% by volume. The upper limit of the filling rate of grinding balls in the container is calculated based on the container's volume, and can be, for example, 65% by volume.

[0060] In the pulverization process, the pulverization time can be, for example, 5 to 15 hours or 8 to 12 hours. This allows the silicon nitride powder to be sufficiently refined.

[0061] In the pulverization process, for example, the material obtained by ball milling can be further pulverized by vibratory milling. The filling rate of the grinding balls in the container during vibratory milling can be, for example, 50–80% by volume, or 60–75% by volume. The pulverization time (pulverization period) during vibratory milling can be, for example, 8–20 hours, or 12–17 hours. This allows for sufficient refinement of the raw silicon nitride powder and adjustment of D97, thereby making it easier to obtain the silicon nitride powder specified in this application.

[0062] As a process for adjusting particle size, dry classification can also be used to obtain silicon nitride powder with a D97 of 2.0 μm or less and (D90-D10) / D50 of 1.70 or less. For example, when it contains agglomerated particles (also called secondary particles) that are formed by agglomerating multiple primary silicon nitride particles, since these particles will increase the overall particle size of the silicon nitride powder, at least a portion of these agglomerated particles can be excluded to adjust the particle size distribution of the silicon nitride powder. In addition, a portion of the larger particles among the primary silicon nitride particles can be excluded to adjust the particle size distribution of the silicon nitride powder.

[0063] Dry classification can be performed by sieving or by an air classifier. An air classifier can be a classifier that uses a swirling airflow of primary and secondary air. For example, the "EVX-1" manufactured by Newmart Industries, Ltd. of Japan can be used as such an air classifier.

[0064] Air classifiers can control the swirling airflow velocity by adjusting operating conditions, such as adjusting the classifying air volume and the louver opening of the air guide vanes. Here, the classifying air volume refers to the amount of air used to generate the swirling airflow within the air classifier. The primary air introduced into the air classifier forms a swirling airflow after passing through the air guide vanes. By introducing the raw silicon nitride powder into the swirling airflow, a large centrifugal force can be applied to coarse particles, thus facilitating classification. Furthermore, by introducing compressed air (secondary air) with a higher pressure than the primary air into the swirling airflow, the classification accuracy can be further improved. Thus, by adjusting the classifying air volume and louver opening in the air classifier, and adjusting the swirling airflow velocity to 170–300 m / s, silicon nitride powder with a D97 value below 2.0 μm and a (D90-D10) / D50 value below 1.70 can be prepared. Such silicon nitride powder, when used to form sintered bodies, exhibits high flexural strength. Furthermore, the Weibull coefficient of the silicon nitride sintered body can be improved.

[0065] An example of the operating conditions for an air classifier is shown below. The classifying air volume can be 1–4 m³ / h. 3 / min, or 1-3m 3 / min. The louver opening of the air guide vanes can be less than 5mm and more than 2mm, for example, within the range of 2 to 3mm. The louver opening refers to the distance between the centers of the louvers. Alternatively, the louver opening can also be expressed as the angle of the louvers. In this case, the angle can be 70°, or 80° to 90°. The louver opening indicates the size of the compressed air (secondary air) inlet. Because when the distance between the centers of the louvers is small, or the angle of the louvers is large, the inlet becomes smaller, thus increasing the pressure and the airflow rotation speed. Furthermore, the secondary air pressure can be 0.2 to 1.0 MPa, or 0.4 to 0.8 MPa. By grading under these conditions, the swirling airflow velocity can be adjusted to 170 to 300 m / s, thereby enabling the high-precision removal of coarse particles that were not fully pulverized during the pulverization process. Moreover, compared to methods such as mixing powders of different particle sizes or adjusting particle size through pulverization, this method allows for the simpler production of the target silicon nitride powder.

[0066] From the viewpoint of promoting the classification of silicon nitride powder and obtaining silicon nitride powder with a smaller D97 and a larger Weibull coefficient in the sintered body, the swirling gas flow velocity can be 170 m / s or higher, 200 m / s or higher, 220 m / s or higher, or 230 m / s or higher. Furthermore, from the viewpoint of improving the yield after classification and increasing production efficiency, the swirling gas flow velocity can also be 300 m / s or lower or 250 m / s or lower. The aforementioned range of swirling gas flow velocities can be 170–300 m / s, 220–300 m / s, or 220–250 m / s. The swirling gas flow velocity can be calculated using the formula V = Q / A, where V is the flow velocity (m / s) and Q is the flow rate (m³ / s). 3 / s), A is the cross-sectional area of ​​the swirling flow field (m 2 The swirling airflow velocity can also be measured, for example, using a thermal airflow converter (trade name: TA10 ZG2d, manufactured by Centronic Co., Ltd.).

[0067] The aforementioned D97 can be adjusted to, for example, below 1.80 μm, below 1.60 μm, or below 1.40 μm. Adjusting the D97 of silicon nitride powder to this range can further suppress the formation of coarse particles after sintering and obtain sintered bodies with higher flexural strength. D97 can be adjusted to, for example, above 0.80 μm, above 0.90 μm, or above 1.00 μm. The range of D97 can be adjusted to, for example, 0.80–2.0 μm, 0.80–1.80 μm, 0.80–1.60 μm, or 0.80–1.40 μm.

[0068] In the particle size adjustment process, D90 can be adjusted to, for example, 1.50 μm or less, 1.30 μm or less, or 1.10 μm or less. Silicon nitride powder with an upper limit D90 in this range, due to its further reduced particle size, can more effectively suppress the formation of coarse particles in the sintered body, thereby obtaining a sintered body with higher flexural strength. Furthermore, D90 can also be adjusted to, for example, 0.30 μm or more, 0.40 μm or more, or 0.50 μm or more. The range of D90 can be adjusted to, for example, 0.30–1.50 μm, 0.50–1.30 μm, or 0.50–1.10 μm.

[0069] In the particle size adjustment process, D50 can be adjusted to, for example, 0.70 μm or less, 0.65 μm or less, or 0.60 μm or less. Silicon nitride powder with an upper limit D50 in this range, due to its further reduced particle size, can more effectively suppress the formation of coarse particles in the sintered body, thereby obtaining a sintered body with higher flexural strength. Furthermore, D50 can also be adjusted to, for example, 0.20 μm or more, or 0.30 μm or more. The range of D50 can be adjusted to, for example, 0.20–0.70 μm, 0.30–0.65 μm, or 0.30–0.60 μm.

[0070] In the particle size adjustment process, D10 can be adjusted to, for example, 0.40 μm or less, 0.30 μm or less, or 0.20 μm or less. Silicon nitride powder with an upper limit of D10 within this range, due to its further reduced particle size, can more effectively suppress the formation of coarse particles in the sintered body, thereby obtaining a sintered body with higher flexural strength. Furthermore, D10 can also be adjusted to, for example, 0.02 μm or more, 0.05 μm or more, or 0.10 μm or more. The range of D10 can be adjusted to, for example, 0.05–0.30 μm, or 0.10–0.20 μm.

[0071] In the particle size adjustment process, the (D90-D10) / D50 value of the silicon nitride powder calculated based on D90, D50, and D10 can be adjusted to, for example, 1.60 or less, or 1.50 or less. When using such silicon nitride powder to manufacture multiple sintered bodies, the deviation in flexural strength of each sintered body can be reduced. In other words, the Weibull coefficient of the sintered body can be improved.

[0072] The value of (D90-D10) / D50 can be adjusted to, for example, 1.30 or higher, or 1.40 or higher. Silicon nitride powder within this (D90-D10) / D50 range exhibits smaller particle size deviations. Therefore, during the manufacture of sintered bodies, the environment in which silicon nitride powder dissolves in the liquid phase of the sintering aid and precipitates again can be further homogenized, more effectively suppressing the increase in particle size deviation of the β-phase particles during growth. Thus, the flexural strength of the obtained sintered body can be further improved. The value of (D90-D10) / D50 of the sintered body can be adjusted to, for example, a range of 1.30 to 1.70, or 1.40 to 1.70.

[0073] Through the above processes, the silicon nitride powder of this embodiment can be manufactured. However, the above manufacturing method is only an example and is not limited thereto. Since the silicon nitride powder of this embodiment has adjusted the values ​​of D97 and (D90-D10) / D50, it is suitable for use as a raw material for sintered bodies with high flexural strength.

[0074] When manufacturing sintered bodies using silicon nitride powder as a raw material, the sintering raw material containing the silicon nitride powder needs to be shaped before sintering. In addition to silicon nitride powder, the sintering raw material may also contain oxide-based sintering aids. Examples of oxide-based sintering aids include Y₂O₃, MgO, and Al₂O₃. The content of oxide-based sintering aids in the sintering raw material can be, for example, 3 to 10% by mass.

[0075] The aforementioned sintering raw materials are pressurized at a molding pressure of, for example, 3.0 to 200 MPa to obtain a molded body. The molded body can be produced by uniaxial pressing or by CIP (Continuous Injection Processing). In some cases, the molding process can simultaneously include both uniaxial pressing and CIP. Furthermore, firing can be performed simultaneously with hot pressing. The firing of the molded body includes two steps: a primary firing step and a secondary firing step, performed in an inert gas atmosphere such as nitrogen or argon. The pressure of the primary firing step can be, for example, 0.7 to 1 MPa. The firing temperature can be, for example, 1700 to 1900 °C or 1750 to 1850 °C. The firing time at this firing temperature can be, for example, 0.5 to 20 hours or 1.5 to 16 hours. The heating rate to the firing temperature can be, for example, 1.0 to 10.0 °C / min.

[0076] In a secondary firing process that uses the sintered body obtained in a primary firing process as the target material, the firing pressure can be, for example, 70 MPa or more, preferably 100 MPa or more. The firing temperature can be, for example, 1650–1850 °C or 1700–1800 °C. The firing time at this firing temperature can be, for example, 0.5–5 hours or 1–2 hours. The heating rate to the firing temperature can be, for example, 1.0–10.0 °C / hour.

[0077] The resulting sintered body exhibits fewer coarse particles and a highly uniform microstructure. Furthermore, due to its sufficiently dense structure, it possesses excellent flexural strength. Additionally, the reduced variation in particle size minimizes performance deviations in the silicon nitride sintered body.

[0078] The flexural strength of the sintered body can be above 920 MPa, 930 MPa, 950 MPa, 960 MPa, 970 MPa, or 980 MPa. Such silicon nitride sintered bodies possess excellent mechanical strength and are suitable for use as components in various industrial applications. The flexural strength of the sintered body is a three-point flexural strength tester, which can be determined according to JIS R 1601:2008 using a commercially available flexural strength testing machine. The flexural strength of the sintered body can be below 1100 MPa. For example, the range of flexural strength for the sintered body can be 920–1100 MPa, 930–1100 MPa, 950–1100 MPa, 960–1100 MPa, 970–1100 MPa, or 980–1100 MPa.

[0079] The fracture toughness (destructive strength) of the sintered body can be 4.5 (MPa / m). 2 ) or above, 4.6 (MPa / m 2 ) or above, 4.7 (MPa / m 2 ) or above 4.8 (MPa / m 2 The silicon nitride sintered body exhibits excellent mechanical strength, making it suitable for use in various industrial components. The fracture toughness of the sintered body can be determined according to JIS R 1607:2015 standard. The fracture toughness of the sintered body can be 6.0 (MPa / m). 2 The fracture toughness value of the sintered body can range, for example, from 4.5 to 6.0 (MPa / m). 2 ), 4.6~6.0 (MPa / m 2 ), 4.7~6.0 (MPa / m 2 ) or 4.8~6.0 (MPa / m 2 ).

[0080] The Vickers hardness of the sintered body can be above 1.400 HV, 1.420 HV, 1.430 HV, or 1.440 HV. Such silicon nitride sintered bodies exhibit excellent wear resistance and are suitable for use in various industrial parts. The Vickers hardness of the sintered body can be measured according to JIS R 1610:2003 standard. The Vickers hardness of the sintered body can be below 1.600 HV. For example, the Vickers hardness range of the sintered body can be 1.400–1.600 HV, 1.420–1.600 HV, 1.430–1.600 HV, or 1.440–1.600 HV.

[0081] Due to the high uniformity of the microstructure, the distribution of bending strength in the aforementioned silicon nitride sintered body is effectively suppressed. The silicon nitride sintered body exhibits a relatively large Weibull coefficient in its Weibull statistical analysis corresponding to its bending strength. The Weibull coefficient corresponding to the bending strength of the silicon nitride sintered body can be, for example, 10.0 or higher, 12.0 or higher, 13.0 or higher, 15.0 or higher, 17.0 or higher, or 20.0 or higher. Furthermore, the Weibull coefficient can be 25.0 or lower. The range of the Weibull coefficient can be, for example, 10.0–25.0, 12.0–25.0, 13.0–25.0, 15.0–25.0, 17.0–25.0, or 20.0–25.0.

[0082] Weibull statistics are used to evaluate the distribution of flexural strength. For silicon nitride sintered bodies, when a Weibull plot is drawn with the failure probability F(σ) as the vertical axis and the flexural strength σ (strength at fracture, flexural strength) as the horizontal axis, the slope m is the Weibull coefficient. The larger the Weibull coefficient, the narrower the distribution of flexural strength, and the closer it is to a normal distribution. The failure probability F(σ) in the Weibull plot can be represented by the following equation (1): F(σ) = 1 - exp [-(σ / η)m] ...(1) In equation (1) above, η is the fitting parameter.

[0083] The above describes several embodiments of this disclosure, but the content of this disclosure is not limited to the above embodiments.

[0084] Example The present disclosure will now be described in more detail with reference to embodiments and comparative examples. However, the present disclosure is not limited to the embodiments described below.

[0085] (Comparative Example 1) <Preparation of raw material silicon nitride powder> A raw material powder was prepared by combining 1 part by mass of silicon powder with 1 part by mass of fluorite. That is, the raw material powder contains 1 part by mass of fluoride (fluorite) per 100 parts by mass of silicon powder. An alumina container was prepared, having a body and a lid, the body having a recess. The raw material powder was filled into the recess. The filling shape of the raw material powder was cuboid, with a filling height of 45 mm. The lid was used to cover the recess of the body, thus containing the raw material powder within the alumina container. The raw material powder contained in the container was then calcined according to the following steps.

[0086] The container holding the raw material powder was placed in an electric furnace and fired according to the following temperature conditions: The temperature was increased from 20°C to 1150°C at a rate of 5°C / min. It was held at 1150°C for 8 hours, then increased to 1450°C at a rate of 0.15°C / min. It was held at 1450°C for 4 hours, then allowed to cool naturally to room temperature. The atmosphere in the electric furnace was nitrogen. The total time from the start of the holding at 1150°C to the end of the holding at 1450°C was 45 hours.

[0087] The obtained ingots were coarsely ground and then wet-milled for 8 hours using an attritor mill. The filling rate of the grinding balls in the attritor mill was set to 70% by volume. They were then dried under a nitrogen atmosphere.

[0088] The pulverized material obtained by wet milling was acid-treated by immersing it in hydrofluoric acid (hydrogen fluoride concentration: 1.6% by mass) at 70°C for 4 hours. Then, the pulverized material was removed from the hydrofluoric acid, washed with water, and dried under a nitrogen atmosphere. In this manner, raw silicon nitride powder (powder a) was obtained.

[0089] (Comparative Example 2) Except for changing the hydrogen fluoride concentration of hydrofluoric acid to 1.8% by mass, the raw material silicon nitride powder (powder b) of Comparative Example 2 was prepared using the same procedures as Comparative Example 1.

[0090] (Comparative Example 3) Except for changing the hydrogen fluoride concentration of hydrofluoric acid to 1.9% by mass, the silicon nitride powder (powder c) of Comparative Example 3 was prepared using the same procedures as Comparative Example 1.

[0091] (Comparative Example 4) Except for changing the hydrogen fluoride concentration of hydrofluoric acid to 1.7% by mass, the silicon nitride powder (powder d) of Comparative Example 4 was prepared using the same procedures as Comparative Example 1.

[0092] (Comparative Example 5) Except for changing the hydrogen fluoride concentration of hydrofluoric acid to 1.4% by mass, the silicon nitride powder (powder e) of Comparative Example 5 was prepared using the same procedures as Comparative Example 1.

[0093] (Comparative Example 6) Except for changing the hydrogen fluoride concentration of hydrofluoric acid to 2.0% by mass, the raw material silicon nitride powder (powder f) of Comparative Example 6 was prepared using the same procedures as Comparative Example 1.

[0094] (Example 1) <Classification of raw silicon nitride powder> Using silicon nitride powder (powder a) from Comparative Example 1 as raw material, silicon nitride powder was obtained by classifying it using an air classifier (manufactured by Nippon Pneumatic Mfg. Co., Ltd., Japan, trade name: EVX-1). The classification conditions are as follows.

[0095] Graded air volume: 1.1m³ 3 / min The louver opening of the main air guide vanes is 2mm. Secondary air pressure: 0.4 MPa Circulating airflow velocity: 230m / s (Example 2) Using silicon nitride powder (powder b) from Comparative Example 2 as raw material, silicon nitride powder was obtained by classifying it using an air classifier (manufactured by Nippon Pneumatic Mfg. Co., Ltd., Japan, trade name: EVX-1). The classification conditions are as follows.

[0096] Graded air volume: 1.1m³ 3 / min The louver opening of the main air guide vanes is 2mm. Secondary air pressure: 0.4 MPa Circulating airflow velocity: 230m / s (Example 3) Using silicon nitride powder (powder c) from Comparative Example 3 as raw material, silicon nitride powder was obtained by classification using an air classifier (manufactured by Nippon Pneumatic Mfg. Co., Ltd., Japan, trade name: EVX-1). The classification conditions are as follows.

[0097] Graded air volume: 1.1m³ 3 / min The louver opening of the main air guide vanes is 2mm. Secondary air pressure: 0.4 MPa Circulating airflow velocity: 230m / s (Example 4) Using the silicon nitride powder (powder d) from Comparative Example 4 as the raw silicon nitride powder, silicon nitride powder was obtained by classification using an air classifier (manufactured by Nippon Pneumatic Mfg. Co., Ltd., Japan, trade name: EVX-1). The classification conditions are as follows.

[0098] Graded air volume: 1.1m³ 3 / min The louver opening of the main air guide vanes is 2mm. Secondary air pressure: 0.4 MPa Circulating airflow velocity: 230m / s (Example 5) Using the silicon nitride powder (powder e) from Comparative Example 5 as the raw silicon nitride powder, silicon nitride powder was obtained by classification using an air classifier (manufactured by Nisshin Engineering Co., Ltd., trade name: AC-20). The classification conditions are as follows.

[0099] Graded air volume: 2.0m³ 3 / min The louver opening of the main air guide vanes is 90°. Secondary air pressure: 0.7 MPa Circulating airflow velocity: 200m / s (Example 6) Using the silicon nitride powder (powder e) from Comparative Example 5 as the raw silicon nitride powder, silicon nitride powder was obtained by classification using an air classifier (manufactured by Nisshin Engineering Co., Ltd., trade name: AC-20). The classification conditions are as follows.

[0100] Graded air volume: 2.4m³ 3 / min The louver opening of the main air guide vanes is 90°. Secondary air pressure: 0.8 MPa Circulating airflow velocity: 300m / s [Determination of α-conversion rate] The α-saturation of silicon nitride powder was determined according to the following procedure. X-ray diffraction of silicon nitride powder was performed using CuK α rays in an X-ray diffraction apparatus (Rigaku, apparatus name: Ultima IV). The α phase is represented by the diffraction line intensities Ia102 of the (102) plane and Ia210 of the (210) plane. The β phase is represented by the diffraction line intensities Ib101 of the (101) plane and Ib210 of the (210) plane. The α-saturation was calculated using the following formula using these diffraction line intensities. The measurement results for each example and comparative example are shown in Table 1.

[0101] Alpha conversion rate (mass%) = (Ia102 + Ia210) / (Ia102 + Ia210 + Ib101 + Ib210) × 100 [Determination of Particle Size Distribution] The particle size distribution of silicon nitride powder was determined by laser diffraction and scattering. The determination was performed according to the method described in JIS R 1629:1997, "Method for determination of particle size distribution of fine ceramic raw materials by laser diffraction and scattering". The particle size distribution was determined as follows: 60 mg of silicon nitride powder was weighed into a 500 mL container. A 20% aqueous solution (2 mL) of sodium hexametaphosphate and 200 g of water were added as a dispersant. The container was placed in an ultrasonic disperser manufactured by Sharp Corporation, and the dispersion was completely submerged for 1 minute. The particle size distribution of the ultrasonically dispersed sample was measured. D10, D50, D90, and D97 were obtained in each example and comparative example. Furthermore, the value of (D90 - D10) / D50 was calculated based on the obtained results. The results are shown in Table 1.

[0102] [Determination of BET specific surface area] The BET specific surface area of ​​silicon nitride powder was determined using nitrogen gas via the BET single-point method according to JIS R 1626:1996 "Determination of specific surface area of ​​fine ceramic powders by gas adsorption BET method". The measurement results of each example and comparative example are shown in Table 1.

[0103] [Determination of Oxygen Content] The oxygen content of the silicon nitride powder was determined as total oxygen. The oxygen content was measured using an oxygen-nitrogen analyzer (manufactured by Horiba Manufacturing Co., Ltd., instrument name: EMGA-920). Specifically, in a helium atmosphere, the silicon nitride powder was heated from 20°C to 2000°C at a heating rate of 8°C / s, and the oxygen content (mass%) in the entire silicon nitride powder was determined by quantitatively releasing oxygen. The measurement results for each example and comparative example are shown in Table 1.

[0104] [Preparation of sintered bodies] 91 parts by weight of silicon nitride powder, 5 parts by weight of Y₂O₃ powder with an average particle size of 1.5 μm, and 4 parts by weight of Al₂O₃ powder with an average particle size of 1.2 μm were mixed in methanol and wet-mixed for 4 hours. The mixture was then dried, and the resulting powder mixture was molded under 10 MPa pressure, followed by CIP molding under 100 MPa pressure. The resulting molded body, along with a filler powder consisting of a mixture of silicon nitride and BN powder, was placed in a carbon crucible and heated to 900°C under vacuum at a heating rate of 10°C / min. Nitrogen gas was then introduced, and the mixture was heated to 1400°C under a nitrogen atmosphere at a heating rate of 5°C / min. The mixture was held at 1400°C for 2 hours, and then heated to a firing temperature of 1800°C at a heating rate of 5°C / min. A primary silicon nitride sintered body was produced by holding the sintered body at 1800°C for 2 hours, then cooling it to 1000°C at a rate of 5°C / min, and then allowing it to cool naturally. A secondary sintering process was then performed by further pressurizing the obtained sintered body to 100 MPa under a nitrogen atmosphere and heating it to 1700°C at a rate of 5°C / hour, then holding it at 1700°C for 1 hour.

[0105] [Determination of the flexural strength of sintered bodies and calculation of the Weibull coefficient] The flexural strength was measured at three points according to JIS R 1601:2008 using a commercially available flexural strength tester (Shimadzu Corporation, device name: AG-2000). The measurements were performed at room temperature (20°C). The results are shown in Table 2. For each example of silicon nitride powder, 20 sintered bodies were prepared, and the Weibull coefficient was calculated based on the distribution of flexural strength of these sintered bodies. The measurements for each example and comparative example were performed using the same method. The results are shown in Table 2.

[0106] [Determination of fracture toughness of sintered bodies] Fracture toughness (KIC) was determined by the IF method according to JIS R 1607:2015 using a commercially available testing apparatus (manufactured by Matsuzawa Co., Ltd., apparatus name: Via-F). The results are shown in Table 2.

[0107] [Determination of Vickers hardness of sintered bodies] Vickers hardness was determined using an electric Vickers hardness tester (manufactured by Matsuzawa Corporation, trade name: Via-F) in accordance with JIS R 1610:2003. The results are shown in Table 2.

[0108] [Observation of the cross-section of the sintered body] A portion of the cross-section of the prepared sintered body was observed using a scanning electron microscope. The results are as follows: Figure 1 as well as Figure 2 As shown. Figure 1 This is a scanning electron microscope image showing a portion of the cross-section of the sintered body prepared using the silicon nitride powder of Comparative Example 4. Similarly, Figure 2 A portion of the cross-section of the sintered body from Example 4 is shown. Figure 1 and Figure 2 By comparison, we found Figure 1 The coarse particles in the sintered body are more than Figure 2 Much.

[0109] [Table 1]

[0110] [Table 2]

[0111] By comparing the examples and comparative examples, it can be confirmed that sintered bodies obtained using silicon nitride powder with D97 and (D90-D10) / D50 values ​​within the range defined in this disclosure as raw materials show an increasing trend in flexural strength compared to sintered bodies obtained using silicon nitride powder from the comparative examples as raw materials. Furthermore, it has been confirmed that when multiple silicon nitride sintered bodies are manufactured using the silicon nitride powder from the examples, the deviation in flexural strength is small, and the Weibull coefficient related to flexural strength increases.

[0112] Industrial utilization potential According to this disclosure, a silicon nitride powder can be provided that can be used to prepare sintered bodies with a large Weibull coefficient and excellent flexural strength. Furthermore, according to this disclosure, a method for manufacturing the aforementioned silicon nitride powder at a lower cost can also be provided.

Claims

1. A silicon nitride powder, In the cumulative particle size distribution of a volume reference measured using a particle size distribution measuring device based on laser diffraction and scattering, the particle size at which the cumulative value from the small particle size side reaches 10% of the total is defined as D10, the particle size at which the cumulative value from the small particle size side reaches 50% of the total is defined as D50, the particle size at which the cumulative value from the small particle size side reaches 90% of the total is defined as D90, and the particle size at which the cumulative value from the small particle size side reaches 97% of the total is defined as D97. D97 is below 2.0μm. And (D90-D10) / D50 is below 1.

70.

2. The silicon nitride powder according to claim 1, wherein, The α-oxidation rate was below 96.0% by mass.

3. The silicon nitride powder according to claim 1 or 2, wherein, The oxygen content is 0.60–1.60% by mass.

4. The silicon nitride powder according to claim 1 or 2, wherein, The specific surface area of ​​BET is 12.0 m². 2 / g or more.

5. The silicon nitride powder according to claim 1 or 2, wherein, The oxygen content (BET specific surface area × D10) is 0.30 to 0.

80.

6. A method for manufacturing silicon nitride powder, wherein, This includes the process of adjusting particle size. In the aforementioned process, in the cumulative particle size distribution of the volume reference measured by the particle size distribution measuring device using laser diffraction and scattering method, the particle size at which the cumulative value from the small particle size side reaches 10% of the total is defined as D10, the particle size at which the cumulative value from the small particle size side reaches 50% of the total is defined as D50, the particle size at which the cumulative value from the small particle size side reaches 90% of the total is defined as D90, and the particle size at which the cumulative value from the small particle size side reaches 97% of the total is defined as D97. To make D97 below 2.0μm, Furthermore, the particle size of the raw silicon nitride powder is adjusted by ensuring that (D90-D10) / D50 is below 1.

70.

7. The method for manufacturing silicon nitride powder according to claim 6, wherein, The particle size adjustment process involves using an air classifier to classify the raw silicon nitride powder under a swirling airflow velocity of 170–300 m / s to adjust the particle size.

8. The method for manufacturing silicon nitride powder according to claim 6 or 7, wherein, The α-oxidation rate of the raw material silicon nitride powder is less than 96.0% by mass.

Citation Information

Patent Citations

  • Silicon nitride powder, silicon nitride sintered compact, and circuit board for electronic component using the sintered compact

    JP2004262756A